FAKTOR-FAKTOR YANG MEMPENGARUHI SETORAN LPPL RADIO PADA LPPL RADIO KABUPATEN/KOTA SE-JAWA TENGAH - Tubagus Muhammad Sadaruddin, 12.5202.0107 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the factors that affect deposit LPPL (Local Public Broadcasting) Radio on Radio LPPL Regency/City in Central Java. Some researchers emphasize the effect of the regulation is a factor, the budget ceiling given by the budget, the number of HR employees and deposit targets mandated by the respective local government district/city. The population in this study was 32 ââLPPL Radio districts/cities in Central Java. In addition, this study uses panel data time series for the past three years, starting in 2011, 2012 and 2013. This study uses multiple methods approach, the approaches are : Pooled Least Square (PLS), Fixed Effect Model (FEM) and Random Effect Model (REM). The model testing uses Chow Test and Hausman Test. The hypothesis testing, conducted through partial test based on t test. The results showed that model tends to use FEM. Based on that estimation model was found that only two variables that were significant namely regulation and deposit targets at 5% significance level. Beside that amaount of human resources was significant at 10% significance level. The rest that is the budget was insignificant. Keywords: Deposits of LPPL Radio, budgets, HR